2002
DOI: 10.1007/3-540-47967-8_56
|View full text |Cite
|
Sign up to set email alerts
|

Surviving Dominant Planes in Uncalibrated Structure and Motion Recovery

Abstract: In this paper we address the problem of uncalibrated structure and motion recovery from image sequences that contain dominant planes in some of the views. Traditional approaches fail when the features common to three consecutive views are all located on a plane. This happens because in the uncalibrated case there is a fundamental ambiguity in relating the structure before and after the plane. This is, however, a situation that is often hard to avoid in man-made environments. We propose a complete approach that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 24 publications
0
51
0
Order By: Relevance
“…8(b)). The same angle is measured as 89.8 • in a reconstruction using (Pollefeys et al 2002). The precise ground truth angle between the targets is unknown.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…8(b)). The same angle is measured as 89.8 • in a reconstruction using (Pollefeys et al 2002). The precise ground truth angle between the targets is unknown.…”
Section: Figmentioning
confidence: 99%
“…9(b). The metric reconstruction using a locally optimal linear algorithm for directly estimating the absolute quadric (Pollefeys et al 2002) is shown in Fig. 9(c).…”
Section: Figmentioning
confidence: 99%
“…However, nodes that share only a few corresponding points with node i are removed from the cluster in order to ensure a minimum nucleus of corresponding points seen by all cameras in the cluster. The minimum cluster and nucleus size required for viable calibration depend on the number of parameters to be estimated at each node [67], [68]. In our experiments, we use a minimum cluster size of 3 cameras and a nucleus of at least 8 corresponding points.…”
Section: A Initializing the Calibrationmentioning
confidence: 99%
“…The approach we favor is based on estimating a 4 × 4 symmetric rank-3 matrix called the absolute dual quadric, which is constrained by the camera matrices and some known properties of each camera's fixed internal parameters (for example, that the elements of the CCD array are square). Detailed descriptions of metricfrom-perspective recovery based on this approach are given by Pollefeys et al [67], [68].…”
Section: A Initializing the Calibrationmentioning
confidence: 99%
“…The chirality constraints can then be applied to resolve this ambiguity unless all points are closer to one viewpoint than the other, in which the motion would be unresolvable [1]. Several methods such as [2], [6], [7] were proposed in order to overcome the planar degeneracy in the epipolar geometry-based SFM by incorporating the knowledge of the coplanarity in the algorithm design. Such works provide sufficient solution to the problem since scene regularities can generally be detected [8].…”
Section: Introductionmentioning
confidence: 99%